PERANCANGAN PRIMER SECARA IN SILICO UNTUK AMPLIFIKASI GEN IGF1 MENGGUNAKAN APLIKASI BIOINFORMATIKA - chan, suwarny; Titi Purnama; Sanatang (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2025)
Insulin-like Growth Factor 1 (IGF1) is a gene that plays a vital role in cell growth and development in mammals. Proper primer design is crucial for successful target gene amplification through PCR technique. This study aims to design and analyze specific primers for IGF1 gene amplification using an in silico approach. The methods employed include sequence analysis using MEGA 11, primer design using Primer3Plus, and primer validation using Clone Manager Demo 9. Evaluation of the designed primers demonstrated optimal characteristics according to PCR parameters, including nucleotide size, melting temperature, and appropriate GC percentage. Secondary structure analysis confirmed the absence of primer-dimer formation and hairpin structures that could potentially reduce amplification effectiveness. In silico analysis showed that the designed primers have high specificity to the target gene and are predicted to amplify a 325 bp DNA fragment. This research has produced primer designs that can be used effectively and specifically for IGF1 gene amplification in subsequent studies https://docs.google.com/document/d/1iPjWY0R-uTUXNQGJCmWf6L1lrg7-IHh6/edit?usp=sharing&ouid=113416817180411207854&rtpof=true&sd=true